2021
DOI: 10.1039/d1sc00692d
|View full text |Cite
|
Sign up to set email alerts
|

A chameleonic macrocyclic peptide with drug delivery applications

Abstract: Head-to-tail cyclized peptides are intriguing natural products with unusual properties. The PawS-Derived Peptides (PDPs) are ribosomally synthesized as part of precursors for seed storage albumins in species of the daisy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Small disulfide-rich peptides can be difficult to study by crystallography, but racemic crystallography in which a mixture of chemically synthesised peptides assembled with all l or all d amino acids improves crystallisation by allowing access to more favoured space groups. 35,36 Thus, to independently determine the tertiary and quaternary structure of PDP-23 for comparison with the water-based solution NMR spectroscopy, 9 we attempted racemic X-ray crystallography. Both PDP-23 and its mirror image, d -PDP-23, were synthesised as described previously using (Fmoc)-based solid phase peptide synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Small disulfide-rich peptides can be difficult to study by crystallography, but racemic crystallography in which a mixture of chemically synthesised peptides assembled with all l or all d amino acids improves crystallisation by allowing access to more favoured space groups. 35,36 Thus, to independently determine the tertiary and quaternary structure of PDP-23 for comparison with the water-based solution NMR spectroscopy, 9 we attempted racemic X-ray crystallography. Both PDP-23 and its mirror image, d -PDP-23, were synthesised as described previously using (Fmoc)-based solid phase peptide synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, a new member of the PDP family was discovered that contains 28 amino acids and two disulfide bonds in a I–II/III–IV ladder-like configuration. 9 NMR spectroscopy showed that this peptide, PDP-23, adopts a unique tertiary structure wherein two loops, each containing a β-sheet bridged by a single disulfide bond, fold together into a V-shaped tertiary structure enclosing a hydrophobic core, more akin to the structures of larger proteins. 9 Additionally, in water PDP-23 self-associates and forms a square prism-shaped symmetrical homodimer quaternary structure by increasing the distance between the loop regions and merging the hydrophobic cores of the two monomers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations